Perbandingan Antara Komunitas Sanggar Mekar Sari Dengan Sanggar Bija Swari: Sebagai Faktor Loyalitas Anggota Pada Periode 2025 - Devika Nova Pratiwi; Pebriansyah Pebriansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to evaluate the comparative process between the Mekar Sari and Bija Swari communities or studios in the process of forming member loyalty during the 2025 period. The main focus of this study is to find elements that contribute to the degree of member loyalty in both communities, both in terms of management, artistic activities, and social interactions among members. The approach applied is a descriptive qualitative method, with data collection through interviews, direct observation, and document collection. The findings show that Sanggar Mekar Sari places more emphasis on elements of family togetherness and regular practice to maintain loyalty, while Bija Swari prioritizes new creativity in its works and opportunities for member loyalty. Both communities each have unique strengths in creating member bonds, but variations in management approaches and artistic views impact the level of loyalty created. This study contributes to understanding the tactics of managing arts communities so that they can maintain member sustainability and competitiveness in the era of modern cultural development